JURIDICAL REVIEW OF THE MERGER PLAN BETWEEN BANK MANDIRI AND BNI IN ANTICIPATION OF GLOBAL COMPETITION IN THE PERSPECTIVE OF CONGLOMERATION AND UNFAIR BUSINESS COMPETITION - Fitri, Fitri; Ayu Lestari, Tiara (IJBLE Scientific Publications Community Inc., 2021)
Banking is one of the increasingly important economic sectors in Indonesia's economic development, especially in facing the era of free trade and globalization, both as an intermediary between the deficit sector and the supply sector as an agent of development. The planned merger of PT Bank Negara Indonesia Tbk and PT Bank Mandiri Tbk was also put forward by the then Minister of Finance with the aim of enlarging the scale of national banking so that it could be aligned with regional banks so that the Indonesian economy could grow the largest in the Association of South East Asia Nations (ASEAN). Although mergers are generally intended for business development based on increasing efficiency, it cannot be denied that mergers can also have consequences that can affect business competition. Other risks that can arise from the merger plan are financial conglomerates against adverse selection and moral hazard, given the excessive risk taking behavior. Judging from the data, in terms of regulations there is indeed no prohibition for banks in Indonesia to have a subsidiary. However, the practice of financial conglomeration has the potential to give birth to an unfair business competition.